Physical activities and breast cancer: a Mendelian randomization study - Lishan Ding; Qingliang Chen; Hao Liang; Meng Shen; Ming Zheng; Zhaojun Li (Archives of Medical Science)
Introduction Previous research suggests a potential association between physical activity (PA) and breast cancer (BC), but the causal relationship remains uncertain. The aim of this study was to explore the causal relationship between PA and BC through Mendelian randomization (MR) analysis.